Licitação Verde como ferramenta de sustentabilidade na aquisição de bens e serviços na Administração Pública - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In face of the importance of environmental preservation, which is fundamental to sustainable livelihood and economic growth, this research aimed to analyze the process es of acquisition of goods and services in the Legislative Assembly of the State of Amazonas (ALEAM) to be able to identify whether the bids held in 2015, were subject to some conditions of sustainability, pointing out the benefits of this procedure to the State. To do so, the techniques of documentary research were applied, as well as online research in official websites and several others that broach the subject, in order to guide the investigation process; it also took into account elements contained in the legislation and theoretical contributions on the topic to map the fundamentals of sustainability procurement as a tool in the acquisition of goods and services in public administration. The results show that although ALEAM does not point out the requirements mentioned in SLTI IN / MP n ° 01/2010 in its Edicts and convening notices, it concerns with environmental issues, using standards, processes and services that address aspects of sustainability in relation to health and safety. In addition, it established permanently the Committee on Environment and Sustainable Development (CAAMA), focused on sustainability and environmental preservation.
Keywords: Licitação Verde; Sustentabilidade; Administração Pública; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIÊNCIAS CONTÁBEIS